Evaluation of the radiological hazard in electron beam welding. Issue 1 (1st February 2021) - Angelini, S.; Cucchi, G.; Mostacci, D.
Abstract : In electron beam welding a very intense pencil beam of electrons is driven onto the base metal, to melt it and produce the welding. In the interaction of the beam with the metal, strong bremsstrahlung emission of X-ray is generated. Here the generation is evaluated, and the KERMA in air at 1 m is predicted. Results show that a significant radiation hazard is present and serious radiation protection measures are needed.